Constraining the Crustal and Mantle Conductivity Structures Beneath Islands by a Joint Inversion of Multi‐Source Magnetic Transfer Functions. Issue 1 (30th December 2022) - Chen, Chaojian; Kuvshinov, Alexey; Kruglyakov, Mikhail; Munch, Federico; Rigaud, Rafael
Abstract: In this study, we present a tool to simultaneously invert multi‐source magnetic transfer functions (TFs), including tippers, solar global‐to‐local TFs originating from the signals due to ionospheric source, and global Q ‐responses originating from the signals due to magnetospheric source. We jointly invert the aforementioned TFs to constrain the local conductivity structures beneath three islands in the Atlantic (Tristan da Cunha), Indian (Cocos), and Pacific (Oahu) Oceans. The recovered conductivity profiles appeared to be consistent with the presence of upper mantle plumes beneath the Tristan da Cunha and Oahu Islands. Our results indicate resistive lithosphere of different thicknesses beneath considered three islands. Besides, new conductivity profiles suggest warmer‐than‐average mantle temperatures and the presence of a small fraction of melt beneath Tristan da Cunha Island. At the same time, the conductivities beneath Cocos Island are in good agreement with estimates expected for ambient mantle conditions. Plain Language Summary: Determining the physical properties of the Earth's interior is a fundamental goal of Geoscience. This goal is especially challenging beneath oceans, where data are sparse and interpretation is complicated by oceanic signals. One key physical property is electrical conductivity, which is sensitive to temperature, water, and melt content. One can constrain the conductivity structure beneath oceans by analyzing magnetic signals measured at island geomagnetic observatories and from satellites. In this study, we jointly analyzed magnetic signals from different sources to constrain the local conductivity structures beneath three islands in the Atlantic (Tristan da Cunha), Indian (Cocos), and Pacific (Oahu) Oceans. The recovered conductivity profiles indicate different thicknesses of the lithosphere beneath the three islands, in agreement with the age of the ocean floor. In addition, our results suggest the presence of mantle up‐wellings (also known as mantle plumes) beneath Tristan da Cunha and Oahu Islands. We explore the significance of the retrieved conductivity variations in terms of mantle temperature and composition. The conductivities beneath Cocos Island are in good agreement with estimates expected for ambient mantle conditions, while our results suggest warmer‐than‐average mantle temperatures and the presence of a small fraction of melt beneath Tristan da Cunha Island. Key Points: We develop an inversion methodology to simultaneously invert magnetotelluric and geomagnetic depth sounding transfer functions We implement the methodology to constrain crustal and upper mantle conductivity beneath three island geomagnetic observatories We interpret the 1‐D conductivity models in terms of lithosphere thickness, mantle thermal structure, water content, and the presence of melt